247 The effect of diet on the microbial community structure and composition in lactating Jersey cows consuming a mixture of straw and dry distillers grains plus solubles in replacement of alfalfa hay. (30th November 2020) - Knoell, Allison; Aluthge, Nirosh; Abbas, Waseem; Bartenslager, Alison; Judy, Jared; Morris, Dennis; Wilson, Hannah C; Herrick, Kevin; Kononoff, Paul J; Fernando, Samodha
Abstract: The rumen microbial community is responsible for producing a majority of the energetic needs for the animal, yet our understanding of the rumen microbiome is in its infancy. To better understand the effect of corn-ethanol coproducts on rumen microbial communities, a replicated 4 × 4 Latin square design study utilizing 12 cows in three squares was conducted to evaluate the replacement of alfalfa hay with a mixture (CoP) containing straw and dried distillers grains plus solubles (DDGS) in lactating Jersey cows. The experimental treatments were (proportions on a dry matter basis): a control diet (CON) containing 18.2% of alfalfa hay with no straw or DDGS. A low coproduct diet (LCoP) containing 12.1% alfalfa, 2.1% straw, and 6.0% DDGS. A medium coproduct diet (MCoP) containing 6.1% alfalfa, 4.2% straw, and 12.1% DDGS. A high coproduct diet (HCoP) containing 6.2% straw, 18.1% DDGS with no alfalfa. Rumen digesta samples were collected via an esophageal tube. No differences were observed for milk production and dry matter intake (P ≥ 0.307) (mean ± SEM) 19.5 kg ± 0.60, 29.6 kg ± 0.91, across treatments, while a decrease in methane was observed (P < 0.01) for the HCoP treatment. The bacterial community was assessed by sequencing the V4 region of the 16S rRNA gene. Additionally, the archaeal community was assessed by sequencing the V4-V5 region of the 16S rRNA gene on the Illumina MiSeq platform. Amplicon Sequence Variants were identified using the DADA2 pipeline. No significant differences were observed for the bacterial (P = 0.334) and archaeal (P = 0.593) communities. Although global effects in microbial community dynamics were not observed, differential taxa were observed with Lachnospiraceae being the major differentially abundant Family. The archaeal community composition demonstrated that Methanobacteriales to be the differentially abundant Order across treatments, and may contribute to methane production.